Mongolia : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that Mongolia's domestic economic performance was mixed during 2000-01 and in the first half of 2002. The severe winters of 2000-01 took a heavy toll on output and rural incomes. Real GDP growth is officially estimated to have declined to about 1 percent a year in 2000-01. Inflation rose to 11 1\2 percent in 2000, as the effects of weather-related decreases in food supplies and higher public utility tariffs were compounded by a 25 percent general increase in civil service wages.